Pengaruh leverage, Likuiditas dan Profitabilitas Terhadap Peringkat Obligasi Pada Perusahaan Manufaktur Yang Terdaftar di PT. Pefindo Periode 2015-2019 - Muhammad Rivandi; Wulandari Gustiyani (Jurnal Ilmiah Pendidikan Scholastic, 2021)
Bond rating information shows the extent to which the company is able to pay its obligations and shows the level risk or security of the bond. The rating of a bond is investment grade, the risk of default on a company’s debt is unavoidable. The purpose of study was to determine how much influence Leverage, Liquidity, and Profitability on Bond Ratings in manufacturing companies listed at PT. PEFINDO for the period 2015-2019. The Sampling technique used purposive sampling method and obtained as many as 65 data. Data obtained from the Indonesia Stock Exchange through the website www.idx.co.id. The analysis method used is panel data regression analysis with the help of the E-Views 8 application. After the chow-test was carried out, it was decided to use the Common Effect Model method. The results showed that Leverage has a negative effect on Bond Ratings. Liquidity has no effect on Bond Ratings, and Profitability has a positive effect on Bond Ratings